Serum differential proteomic profiling of patients with isolated methylmalonic acidemia by iTRAQ - Li, Sitao; Shi, Congcong; Cai, Yao; Gu, Xia; Xiong, Hui; Liu, Xiaoyu; Zhang, Yinchun; Xiao, Xin; Ma, Fei; Hao, Hu (Frontiers in Genetics, 2022)
Isolated methylmalonic acidemia (MMA) is an inherited organic acid metabolic disorder in an autosomal recessive manner, caused by mutations in the methylmalonyl coenzyme A mutase gene, and the isolated MMA patients often suffer from multi-organ damage. The present study aimed to profile the differential proteome of serum between isolated MAA patients and healthy control. The in vivo proteome of isolated MAA patients and healthy subjects was detected by an isobaric tag for relative and absolute quantitation (iTRAQ). A total of 94 differentially expressed proteins (DEPs) were identified between MMA patients and healthy control, including 58 up-regulated and 36 down-regulated DEPs in MMA patients. Among them, the most significantly up-regulated proteins were CRP and immunoglobulins, and the top five most significantly down-regulated proteins were all different types of immunoglobulins in MMA patients. GO analysis showed that these DEPs were mainly enriched in immune-related function membrane protein-related function. KEGG revealed that these DEPs were mainly enriched in lysosome and cholesterol metabolism pathways. Also, these DEPs were predicted to contribute to lipid metabolic diseases. We addressed the proteomes of isolated MMA patients and identified DEPs. Our study expands our current understanding of the MMA, and the DEPs could be valuable for designing alternative therapies to alleviate MMA symptoms.